تعزيز الصّحّة النّفسيّة في ضوء مقاصد الشّريعة الإسلاميّة: دراسة تأصيليّة وقائيّة - Muneer Ali Abdul Rab; Setiyawan Gunardi; Baidar Mohammed Mohammed Hassan; Hakim Ebrahim Abdul Jabbar Al-Shamiri (Faculty of Syariah and Law, Universiti Sains Islam Malaysia, 2026)
International Conference of Postgraduate Students and Academics in Syariah and Law 2025 (INPAC 2025) “Advancing Malaysia Madani through Global Shariah and Legal Research.” Organized by the Faculty of Syariah and Law, Universiti Sains Islam Malaysia (USIM)